DNA interactions of cisplatin tethered to the DNA minor groove binder distamycin - Loskotová, H; Brabec, V (European journal of biochemistry, 1999)
Modifications of natural DNA in a cell-free medium using cisplatin tethered to the AT-specific, minor groove binder distamycin, were studied using various methods of biochemical analysis or molecular biophysics. These methods include: binding studies using differential pulse polarography and flameless atomic absorption spectrophotometry, mapping DNA adducts using a transcription assay, use of ethidium bromide as a fluorescent probe for DNA adducts of platinum, measurement of DNA unwinding by gel electrophoresis, measurement of CD spectra, an interstrand cross-linking assay using gel electrophoresis under denaturing conditions, measurement of melting curves with the aid of absorption spectrophotometry and the use of terbium ions as a fluorescent probe for distorted base pairs in DNA. The results indicate that attachment of distamycin to cisplatin changes several features of the DNA-binding mode of the parent platinum drug. Major differences comprise different conformational alterations in DNA and a considerably higher efficiency of the conjugated drug to form in DNA interstrand cross-links. Cisplatin tethered to distamycin, however, coordinates to DNA with similar base sequence preferences as the untargeted platinum drug. The results point to a unique profile of DNA binding for cisplatin-distamycin conjugates, suggesting that tethering cisplatin to minor groove oligopeptide binders may also lead to an altered biological activity profile.
Keywords: interkalátory; ethidium; Protein Binding; sekvence nukleotidů; adukty DNA; Nucleic Acid Conformation; protinádorové látky; DNA-Binding Proteins; distamyciny; Transcription, Genetic; reagencia zkříženě vázaná; DNA, Superhelical; DNA vazebné proteiny; elektroforéza v polyakrylamidovém gelu; Circular Dichroism; Ethidium; molekulární modely; genetická transkripce; Models, Molecular; Time Factors; bezbuněčný systém; vazba proteinů; konformace nukleové kyseliny; Electrophoresis, Polyacrylamide Gel; DNA Adducts; cirkulární dichroismus; časové faktory; Peptides; Intercalating Agents; DNA; peptidy; cisplatina; Cross-Linking Reagents; Base Sequence; Cell-Free System; Distamycins; Cisplatin; superhelikální DNA; Antineoplastic Agents